Metagenomic Analysis of Plant Viruses Associated With Papaya Ringspot Disease in Carica papaya L. in Kenya - Mumo, Naomi Nzilani; Mamati, George Edward; Ateka, Elijah Miinda; Rimberia, Fredah K.; Asudi, George Ochieng’; Boykin, Laura M.; Machuka, Eunice M.; Njuguna, Joyce Njoki; Pelle, Roger; Stomeo, Francesca (Frontiers in Microbiology, 2020)
Carica papaya L., is an important fruit crop grown by small and large-scale farmers in Kenya for local and export markets. However, its production is constrained by papaya ringspot disease (PRSD). The disease is believed to be caused by papaya ringspot virus (PRSV). Previous attempts to detect PRSV in papaya plants showing PRSD symptoms using enzyme linked immunosorbent assay (ELISA) and Reverse transcriptase (RT)-PCR procedures with primers specific to PRSV, did not yield conclusive results. Therefore, the nature of virus(es) responsible for the PRSD was elucidated in papaya leaves collected from 22 counties through Illumina MiSeq next-generation sequencing (NGS) and validated by RT-PCR and Sanger sequencing. Viruses were detected in 38 out of the 48 leaf samples sequenced. Sequence analysis revealed the presence of four viruses: a Potyvirus named Moroccan watermelon mosaic virus (MWMV), and three viruses belonging to the genus Carlavirus. The Carlaviruses included Cowpea mild mottle virus (CpMMV), and two putative Carlaviruses, closely related but distinct from cucumber vein-clearing virus (CuVCV) with amino acid and nucleotide sequence identities of 75.7-78.1 % and 63.6-67.6 %, respectively, in the coat protein genes. In reference to typical symptoms observed in the infected plants, the two putative Carlaviruses were named papaya mottle-associated virus (PaMV) and papaya mild mottle-associated virus (PaMMV). Surprisingly and in contrast to previous studies in other parts of world, PRSV was not detected. Majority of the viruses were detected as single viral infection, while a few were found infecting with another virus for example MWMV and PaMV. Furthermore, the NGS and RT-PCR analysis identified MWMV to be strongly associated with ringspot symptoms on infected papaya fruits. This study has provided the first complete genome sequences of these viruses isolated from papaya in Kenya, together with primers for their detection, an important step towards the design of long-term, sustainable disease management strategies.